15 FRAILTY AND ADVERSE OUTCOMES IN HIP FRACTURE PATIENTS. (25th October 2022) - Small, C; Sullivan, R; O'Hanlon, S; Cooney, M T; Doyle, R
Abstract: Background: Frailty is highly prevalent in older hip fracture patients, conferring greater risk of poorer outcomes including increased Length of Stay (LOS), Nursing Home (NH) placement and mortality Methods: This prospective observational study took place in a large university hospital with a daily trauma list and an established orthogeriatric service. We compared 3 different screening tools; Rockwood Clinical Frailty Scale (CFS), Zuckerman's Functional Recovery Score (FRS) and New Mobility Score (NMS) and their ability to predict outcomes in hip fracture patients. Participants included all hip fracture patients (>/= 60 years old) admitted to the orthopaedic ward from 2016-2018. Scores were assigned by an ortho-geriatrician and were analysed at admission and at 1 year. Results: Increasing frailty scores were associated with increased mortality, LOS and NH admission rates. Those with a CFS of 4-6 had an increased risk of mortality compared to those with a CFS of 1-3 (OR:3.81, CI 2.15-6.76). Those with a CFS of 7-9 demonstrated increased risk of mortality compared to those without frailty (OR: 8.75, CI 4.58-16.72). Patients with mild-moderate frailty (CFS 4-6) were 5 times more likely to require NH at 1-year (OR 5.09, CI 3.03-8.56) and those with severe frailty (CFS 7-9) were 7 times more likely to be in a NH at 1-year (OR 7.03, CI 3.82-12.94). The moderate frailty group had an inpatient stay 16 days longer than the non-frail group and the severe frailty group, 26 days longer than the non-frail group. Results were similar for FRS and NMS and when adjusted for age. Comparing the discrimination of the different measures for predicting survival, analysis of receiver operating characteristic curves revealed - 0.73 (CFS), 0.72 (NMS) 0.74 (FRS). Interestingly, the mortality rate for men was 32% compared to 21% for females (OR: 1.75 p=0.005). Conclusion: Assessing frailty with a standardised protocol could reliably estimate the risk of adverse outcomes in hip fracture patients.